A leitura do texto escrito pela escrita de leitores: uma abordagem da prática de leitura em sala de aula - Pedrosa, Nilma Alves (2015)
This thesis thematizes the effort to identify a model of reading practice, able to focus on the proficient learning principles, guided by fundamentals of Linguistics Textual socio-cognitiveinteractive part, contribute to explain necessary conceptions through which the representations of these practices were to contribute to the textual reading-production and exceeds the limits of a pedagogical practice oriented pedagogy inherited from the distant past. Points out that the starting point of the survey is woven into teaching process this researcher who dared to use their own prior knowledge and also intuitively to turn those students in "readers." And so it happened, so that the qualitative character that now the topic is covered focused on the scientific conception of "reading strategies" for 9th graders of elementary school. The first movement is investigated models and strategies that guided reading instruction for our traditional schools and it follows, through a review procedure, the theoretical foundations proposed by the language of our modern times, compared to awareness of experiments by modeling -escultura of literary characters of the work of the Auto da Barca Gil Vicente Hell. The following is the order that the another new alinear character model, user-centered-learner comprised both the teaching and learning of reading through three stages: pre-reading, reading and post-reading. Each of these knowledge production moves by student-learners was designed sequenced way and they followed oriented activities for the purpose of identifying the satisfaction or efficiency as to the uses of language resources and not linguistic. The sequence of activities was considered to be an efficient model to easily moldable curricular adaptations to meet the needs of students in the resolution of the activities and effective to present a configuration that allowed proficient students and / or not proficient in reading-production develop texts strategies in solving activities, demonstrating competence and increasing rate in prior knowledge about the topic of the reading of literary texts (good and evil). The physical arrangement of modeling-carving literary characters, as a motto for writing, presented an adequate level of usability to meet the students. It can be said that the model created alinear proved consistent with the needs of students to collect the information, considering their statements of satisfaction for having participated in the reading workshop. In addition, the studio seemed to be in accordance with the building of a social-cognitive-interactive reading teaching model construction and (re) construction of knowledge in view of the activities, especially the modeling-carving characters, such as tone for writing efficient, effective and satisfactory for student learning, because these allowed, for example, demonstrate competency and proficiency. It is hoped that this model contribute to the educational process, even though it was aware that its use in the classroom does not guarantee by itself, student learning